Australian Muslim Citizens: Questions of Inclusion and Exclusion, 2006-2020 - Kabir, Nahid Afrose (Australian Journal of Islamic Studies, 2020)
Muslims have a long history in Australia. In 2016, Muslims formed 2.6 per cent of the total Australian population. In this article, I will discuss Australian Muslims’ citizenship in two time periods, 2006–2018 and 2020. In the first period, I will examine Australian Muslims’ identity and sense of belonging, and whether their race or culture have any impact on their Australian citizenship. I will also discuss the political rhetoric concerning Australian Muslims. In the second period, 2020, I will examine Australian Muslims’ placement as returned travellers during the COVID-19 period. I conclude that, from 2006 to 2018, Islamophobia was rampant in “othering” many Australian Muslims. And in 2020 the Australian government has adopted a policy of inclusion by repatriating its citizens (both Muslims and non-Muslims), but with the COVID-19 crisis, a new dimension of discrimination has been added onto ethnic minorities – in this case Bangladeshi Australians who are mostly Muslims. They are now looked upon as the “other quarantined” or “detained Australian citizens”.